Do football match outcomes impact stock prices of firms of the same geographic area? Evidence from Germany - Pasanen, Jami (My University, 2016)
Traditional finance posits that stock returns are determined by the underlying firm’s fundamentals alone, resulting in market efficiency. In contrast, behavioral finance states that investor irrationality and peoples’ psychological tendencies impact prices and therefore, markets are inefficient. The dependence between football match results and stock prices has been studied for the last decade. Previous studies have shown a relation between match outcomes and stock price movement, supposedly stemming from changes in investor mood brought on by the match outcomes. This study undertakes a firm-level examination, in which match outcomes of six German football teams from the season 2006/07 to 2014/15 are regressed against stock returns of firms whose headquarters locate geographically near the football teams. In addition to a general win/draw/loss effect, an important match factor, a home/away factor and a goal difference factor are examined. Moreover, trading volume changes from on-season periods to off-season periods are compared. The results show no visible relation between stock returns and match wins, draws or losses. When dividing the outcomes according to home- and away-games, important and unimportant matches or goal difference within a match, no distinct relation is noticeable either. Trading volumes are higher during on-season than they are off-season, which espescially taking the other results into consideration, may be due to lower overall trading volumes in the summer rather than the information content of the football matches. The empirical results of this master’s thesis imply that football match outcomes do not have a sufficiently strong impact on investor mood for them to lead to predictable stock price reactions for local firms.
Keywords: Football; Investor sentiment; Behavioral finance; Market efficiency; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|